Integrated renewable energy micro-grid for meeting peak hours demand - Aznan, Khairil Azhar; Khan, Sheroz; Yaacob, Mashkuri; Khalifa, Othman Omran; Aboadla, Ezzidin Hassan Elmabrouk; Tohtayong, Majdee; Khalil, Ashraf; Muhaisen, Naser A.N.; Tan, Nadia Mei Lin (Institution of Engineering and Technology, 2018)
In the TNB-based conventional system, the power demand varies randomly depending upon seasons and months of the year including festive occasions, reaching peak in some hours of days of some months. Sometime a heavy demand (in MW) falls at a time of a day. Such heavy energy demands need to be transported from far-away power stations over long lengthy transmissions causing energy loss not less than 20% in most of the cases. This paper presents load demand variation scenario, identifying peaks, and finally suggesting a strategy for meeting the peak demand from Renewable Energy Sources (RES) of solar and wind. An integrated RES-based microgrid is suggested with analytical and simulation results showing how the peak demand is being met from alternative sources of solar. The results of this paper find applications in suggesting RES-based generations for distributed locations within the low-voltage distribution network of Malaysian Electric Utility Tenaga Nasional Berhad.